A Framework for Search as Learning Experiments: Design, Implementation, and Usability Insights - Silva, Joel H. N. de O.; Neto, Alfredo; Rosado, Breno; Machado, Marcelo; Souza, Jairo F. de; Siqueira, Sean W. M. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2025: Anais do XXXVI Simpósio Brasileiro de Informática na Educação, 2025)
Search as Learning (SAL) explores how users engage with search systems to acquire knowledge and develop understanding. Despite advances in SAL, the lack of general-purpose tools hinders reproducibility and standardization in experimental studies. This paper presents a framework to support researchers in designing SAL experiments, encompassing task creation, data collection, and learning assessment. To evaluate the proposal, we conducted a usability study with 12 participants, which yielded a score of 83.07, indicating excellent usability. Feedback of the participants also provided suggestions for improvement, guiding future development. This work contributes to strengthening methodological practices and fostering reproducibility in SAL research.